2016
DOI: 10.18006/2016.4(5).533.540
|View full text |Cite
|
Sign up to set email alerts
|

Evalution of “indirect fluorescent antibody test‟ as potential screening test for Mycobacterium avium subspecies paratuberculosis using milk of lactating domestic livestock

Abstract: In the present study, Indirect Fluorescent antibody test (iFAT) has been used as the "screening test" for the detection of MAP bacilli in the milk samples of lactating domestic livestock. A total of 372 milk samples from lactating animals were screened by iFAT and results were compared with microscopy of milk samples and milk ELISA test. Comparative analysis of the results of three tests showed that iFAT had fairly good sensitivity (84.7%) and specificity (90.4%), with respect to ZN staining (microscopy) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The results of screening of anti-MAP antibodies by latex agglutination test are shown in Table1, Figure1, 2 and 3. The present investigation was in consonance with the findings ofSingh et al (2016) who observed 51.4% infection in bovine milk samples and with 50.9% infection in paneer samples(Stephen et al, 2016).…”
supporting
confidence: 93%
“…The results of screening of anti-MAP antibodies by latex agglutination test are shown in Table1, Figure1, 2 and 3. The present investigation was in consonance with the findings ofSingh et al (2016) who observed 51.4% infection in bovine milk samples and with 50.9% infection in paneer samples(Stephen et al, 2016).…”
supporting
confidence: 93%
“…Test was performed as per Singh et al (2016a). Briefly, smears were prepared on clean slides from (20 µl commercial milk) samples, air dried at room temperature and heat fixed.…”
Section: Indirect Fluorescent Antibody Test (I_fat)mentioning
confidence: 99%
“…screening of milk and milk products and to estimate bio-incidence of MAP Singh et al, 2016a;Singh et al, 2016b;Singh et al, 2016c). Present study first time used both traditional and newly developed and standardized serological and molecular tests (microscopy, IS900 PCR, i_ELISA, d_ELISA, LAT and i_FAT) to estimate bio-incidence of MAP in liquid pasteurized milk and milk products (flavoured milk and milk powder) made from pasteurized milk and sold by 10 leading commercial market brands in Mathura and Agra districts of South UP in North India.…”
Section: Introductionmentioning
confidence: 99%
“…Test was performed as per Singh et al, (2016a). Briefly, smears were prepared on clean slides from (20 µl commercial milk and milk products), air dried and heat fixed.…”
Section: Indirect Fluorescent Antibody Test (Ifat)mentioning
confidence: 99%